GEOCHEMICAL PROPERTIES OF MACROELEMENTS IN IRRIGATED LIGHT CALCISOLS (Scientific journal of the Fergana State University, 2024)
In this article, it's determined the chemical macroelement composition of irrigated light calcisols formed in Fergana region. Their background quantities were worked out and the geochemical properties of these elements were studied depending on their quantities. Also, in order to study the fertility of these soils, the migration, accumulation and other geochemical properties of the elements in the genetic layers of the soil were studied. The studied elements are: Na, K, Ca, Fe, Rb, Sr, Ba.